2019
DOI: 10.1177/2056305118824199
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Indirect Information Disclosure on Social Network Sites

Abstract: This research investigates user awareness and attitudes toward potential inferences of information posted on social network sites (SNSs). The study reports how user attitudes change after exposure to inferences made based upon information they have disclosed on an SNS, namely, on Facebook. To demonstrate this, two sub-studies involving three focus group sessions were conducted with Facebook users. In the first sub-study, the users received a general introduction to information that can be inferred from posts b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
(100 reference statements)
0
8
0
1
Order By: Relevance
“…Since earlier research has indicated that users are unaware of institutional privacy (Padyab et al 2016(Padyab et al , 2019, we were especially intrigued by its mention in interviews conducted before the scandal. The first series of interviews revealed that although young adults do not have a full understanding of how economic surveillance actually operates, about two-thirds of the participants did appear to be aware of its occurrence even before the CA scandal broke out.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Since earlier research has indicated that users are unaware of institutional privacy (Padyab et al 2016(Padyab et al , 2019, we were especially intrigued by its mention in interviews conducted before the scandal. The first series of interviews revealed that although young adults do not have a full understanding of how economic surveillance actually operates, about two-thirds of the participants did appear to be aware of its occurrence even before the CA scandal broke out.…”
Section: Resultsmentioning
confidence: 96%
“…In other words, they tend to be concerned about their social visibility-privacy from peers, family, employers, and others (Sujon 2018). But sharing information with family, friends, and others on social media also allows companies providing the service to access their data (Andrejevic 2013;Fisher 2018;Fuchs 2012;Jansson 2012;Padyab et al 2019). The latter constitutes institutional privacy-"how institutions such as governments, banks and businesses, use or misuse the personal information" (Raynes-Goldie 2010).…”
Section: Social and Institutional Privacymentioning
confidence: 99%
See 1 more Smart Citation
“…(Mittlerweile scheint es sogar möglich zu sein, auf Fotos die sexuelle Orientierung eines Menschen mit Algorithmen automatisch ablesen zu können; Wang & Kosinski, 2018. ) Sobald Menschen allerdings ein Einblick in solche latenten Profile ermöglicht wird, erhöht dies hingegen ihre Privatheitssorgen (Padyab et al, 2016). Zweitens könnte es auch daran liegen, dass Menschen selten tatsächlich negative Erfahrungen sammeln: Zum Beispiel gaben 2011 nur 2% aller Europäer an, dass schon einmal ihre Identität geklaut worden wäre (European Commission, 2011).…”
Section: Analyseunclassified
“…Data privacy management is largely placed on the shoulders of the individual, typically through the acceptance of (2015) approach to gauge public perception of privacy values and how individuals protect their digital information. Empirical studies on privacy and user agency within systems and networks have been conducted to understand the privacy paradox and counterproductive calculations of a privacy calculus or cost-benefit analysis (Acquisiti et al, 2016; Barnes, 2006;Gerber et al, 2018;Marwick & Hargittai, 2019;Padyab et al, 2019). In these examples, the individuals are assessed for their understanding of how their digital privacy can be invaded, but these tests do not aid in the issue with technology that anonymously produces data and knowledge about them.…”
Section: Theoretical Frameworkmentioning
confidence: 99%